In vitro binding of purified murine ecotropic retrovirus envelope surface protein to its receptor, MCAT-1. - Davey, R A (1997)
An amino-terminal portion of the Friend murine leukemia virus (MLV) envelope surface protein [SU, residues 1 to 236 [SU:(1-236)]] and its receptor, MCAT-1, were each purified from insect cells after expression by using recombinant baculoviruses. Friend SU:(1-236) bound specifically to Xenopus oocytes that expressed MCAT-1 with an affinity (Kd, 55 nM) similar to that of viral SU binding to permissive cells. Direct binding of Friend SU:(1-236) to purified MCAT-1 was observed in detergent and after reconstitution into liposomes. Analysis of binding demonstrated that MCAT-1 and Friend SU:(1-236) interact with a stoichiometry of near 1:1. These findings demonstrate that the amino-terminal domain from the SU of ecotropic murine retroviruses contains an MCAT-1 binding domain.